Subcritical Water Extraction of Essential Oils from Indonesia Basil (Kemangi) Leaf: Effects of Temperature and Extraction Time on Yield and Product Composition - Siti Zullaikah (Seminar Nasional Teknik Kimia Kejuangan, 2015)
This study investigated the extraction of essential oils from Indonesia basil (kemangi) leaf which have a potential antibacterial agent using subcritical water. Effects of temperature and extraction time on yield and product composition of basil oil obtained were study systematically. In this work, experiments were performed in a tubular stainless steel reactor at temperature from 150oC to 215oC for 1 to 9 h of extraction at a certain pressure (P= 40 bar)used fresh basil leaf. The yield and product composition of basil oils obtained were affected by temperature and extraction time. The yield of basil oil increased with increasing extraction time. However, yield of basil oil decreased from 1.41% to 1.2% with increasing temperature from 200oC to 215oC for 9 h of extraction time. The composition of essential oils obtained were varied depending on the temperature of extraction. Components in the basil oil which have an antibactial agent such as 1,8 Cineole, Tricosane and Eugenol were identified using subcritical water at temperature 200oC.